THE STATE AND PROSPECTS OF TRAINING SPECIAL TEACHERS IN MODERN CONDITIONS - Абаева, Галия; Оразаева, Гульжан; Лиходедова, Людмила (Pedagogy and Psychology, 2023)
The article presents a comparative analysis of the special teachers’ training in Kazakhstan and abroad. For comparison an analysis of the training of special teachers in Germany, Finland, the Netherlands and Sweden was carried out. The article analyzes the trends and prospects for the training of teaching staff to work in an inclusive environment. The authors clarified and grouped the requests of teachers implementing inclusive educational practice. Grouped and clarified the requests of teachers of special educational institutions and teachers of secondary schools. The results of the study can be used to update the educational programs of pedagogical specialties.